Preparation method and application of porous TiC nanotube array

CN119038552BActive Publication Date: 2026-10-23NORTHWEST INSTITUTE FOR NONFERROUS METAL RESEARCH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411181997.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2026-10-23
Estimated Expiration
2044-08-27

AI Technical Summary

Technical Problem

该方法采用无定形碳原位热还原工艺,以聚乙二醇热分解产生的无定形碳作为还原剂,实现低热还原温度和短反应时间下原位制备多孔TiC纳米管阵列,有效保证了多孔TiC纳米管阵列的结构完整性,获得具有大比表面积和良好导电性的多孔TiC纳米管阵列,解决了现有技术中大比表面积的多孔TiC阵列制备困难、难以保持多孔阵列结构完整性的难题

Benefits of technology

[0020]1、本发明采用无定形碳原位热还原工艺,以高分子量聚乙二醇热分解产生的无定形碳作为还原剂,实现低热还原温度和短反应时间下原位制备多孔TiC纳米管阵列,有效保证了多孔TiC纳米管阵列的结构完整性,避免产物出现团聚、过度生长导致比表面积过低。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a preparation method and application of a porous TiC nanotube array, and relates to the following steps: (1) taking a titanium base as an anode and a platinum sheet as a cathode, and growing amorphous TiO2 nanotube arrays on the surface of the titanium base through anodic oxidation; (2) heat-treating to obtain a crystalline TiO2 NTs / Ti precursor; and (3) embedding the TiO2 NTs / Ti precursor in titanium powder and polyethylene glycol powder, and then heat-treating to form the porous TiC nanotube array. The application further discloses application of the porous TiC nanotube array as a catalyst carrier in the field of photoelectrocatalysis. The amorphous carbon generated through thermal decomposition of polyethylene glycol is used as a reducing agent through an in-situ thermal reduction process, so that the porous TiC nanotube array is prepared in-situ at a low thermal reduction temperature and a short reaction time, the structural integrity of the porous TiC nanotube array is ensured, the porous TiC nanotube array has a large specific surface area and good conductivity, and the porous TiC nanotube array exhibits excellent performance as a carrier material in the field of photoelectrocatalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalyst support preparation technology, specifically relating to a method for preparing and applying porous TiC nanotube arrays. Background Technology

[0002] Developing metal compounds with high conductivity and large electrochemically active surface areas is essential for their use as catalyst supports. Titanium carbide, with the chemical formula TiC, has a face-centered cubic structure and exhibits high conductivity and good corrosion resistance, making it considered an ideal catalyst support material. Its preparation typically involves reacting a mixture of titanium powder (obtained by hydrogen reduction of TiO2) and carbon at high temperatures, or by mixing and pressing TiO2 and carbon powder into blocks, followed by carbonization in an electric furnace at 1700℃–2100℃ for 10–24 hours.

[0003] The hydrogen reduction method is complex and difficult to operate, resulting in challenges in precise product quality control, high costs, and difficulties in industrial-scale production. Traditional carbothermic reduction of TiO2 requires high temperatures and prolonged holding times, leading to large agglomeration of the product, excessive particle growth, and a low specific surface area. Therefore, there is a need to develop a simpler method for preparing TiC supports with a large specific surface area at low reaction temperatures. Summary of the Invention

[0004] The technical problem to be solved by this invention is to provide a method for preparing porous TiC nanotube arrays, addressing the shortcomings of the prior art. This method employs an in-situ thermal reduction process using amorphous carbon generated from the thermal decomposition of polyethylene glycol as a reducing agent. This achieves in-situ preparation of porous TiC nanotube arrays at low thermal reduction temperatures and short reaction times, effectively ensuring the structural integrity of the porous TiC nanotube arrays. This results in porous TiC nanotube arrays with large specific surface area and good conductivity, solving the problems of difficulty in preparing porous TiC arrays with large specific surface area and difficulty in maintaining the structural integrity of the porous arrays in the prior art.

[0005] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is: a method for preparing porous TiC nanotube arrays, characterized in that the method includes the following steps:

[0006] Step 1: Using a titanium substrate as the anode and a platinum sheet as the cathode, an amorphous TiO2 nanotube array is grown on the surface of the titanium substrate using an anodic oxidation process.

[0007] Step 2: Heat-treat the titanium substrate with amorphous TiO2 nanotube arrays grown on the surface in Step 1 in air to obtain crystalline TiO2 NTs / Ti precursor;

[0008] Step 3: Using titanium powder and polyethylene glycol powder, the crystalline TiO2NTs / Ti precursor obtained in Step 2 is embedded in a magnetic boat in the following order: titanium powder-polyethylene glycol powder-TiO2NTs / Ti precursor-polyethylene glycol powder-titanium powder. Then, it is placed in a tube furnace and heat-treated in an inert atmosphere to form a porous TiC nanotube array on the surface of the titanium matrix.

[0009] In the heat treatment process following embedding in this invention, polyethylene glycol powder undergoes thermal decomposition at high temperature, generating a large amount of amorphous carbon. This provides a high-concentration reducing atmosphere for the TiO2 NTs / Ti precursor. Simultaneously, loosely packed titanium powder "locks" in the amorphous carbon generated from the decomposition of polyethylene glycol powder, prolonging the residence time of amorphous carbon on the surface of the TiO2 NTs / Ti precursor. Under a continuous high-concentration reducing atmosphere, the small-molecule amorphous carbon can rapidly enter the TiO2 lattice, effectively reducing the TiC preparation temperature and reaction time, and forming a porous TiC nanotube array with a large specific surface area and good conductivity on the titanium matrix surface.

[0010] The above-mentioned method for preparing a porous TiC nanotube array is characterized in that the titanium substrate in step one is titanium foil or porous titanium, and the porous titanium is titanium mesh, sintered porous titanium, titanium felt or foam titanium.

[0011] The above-mentioned method for preparing a porous TiC nanotube array is characterized in that the electrolyte used in the anodic oxidation process in step one is an ethylene glycol-H2O-ammonium fluoride system, wherein the mass content of ethylene glycol is 94.5% to 99.45%, the mass content of H2O is 0.5% to 5%, and the mass content of ammonium fluoride is 0.05% to 0.5%.

[0012] The above-mentioned method for preparing a porous TiC nanotube array is characterized in that the electrolysis potential of the anodic oxidation process in step one is 50V to 90V, and the electrolysis time is 0.5h to 3h.

[0013] This invention achieves a dynamic equilibrium between the three reactions by controlling the proportion of H2O and the electrolysis potential in the electrolyte of the anodic oxidation process, thereby obtaining a high-quality TiO2 nanotube array structure. By controlling the electrolysis time, the length of the nanotubes can be controlled, effectively adjusting the thickness of the TiO2 nanotube array on the surface of the titanium substrate.

[0014] The above-mentioned method for preparing a porous TiC nanotube array is characterized in that the heat treatment temperature in step two is 300℃~600℃, and the heat treatment time is 0.5h~3h. This invention, by controlling the heat treatment temperature and time of the titanium substrate, improves the crystallinity of TiO2 while ensuring the integrity of the TiO2 nanotube array, thereby obtaining a TiO2 nanotube array with good lattice integrity, providing a stable lattice structure for the infiltration of amorphous carbon.

[0015] The above-mentioned method for preparing a porous TiC nanotube array is characterized in that the molecular weight of the polyethylene glycol powder in step three is 2000-10000. This invention utilizes the in-situ thermal decomposition of high-molecular-weight polyethylene glycol at high temperatures. The strong intermolecular interactions of high-molecular-weight polyethylene glycol increase its thermal decomposition temperature. By controlling the high molecular weight of the polyethylene glycol powder, it ensures that a large amount of amorphous carbon is produced through thermal decomposition at high temperatures, thus achieving the in-situ preparation of a porous TiC nanotube array at low thermal reduction temperatures and short reaction times.

[0016] The above-mentioned method for preparing a porous TiC nanotube array is characterized in that the inert atmosphere in step three is nitrogen or argon.

[0017] The above-mentioned method for preparing a porous TiC nanotube array is characterized in that the heat treatment process in step three is as follows: first, heating to 350℃ at a heating rate of 5℃ / min and holding at that temperature for 0.5h, followed by heating to 700℃~900℃ at a heating rate of 10℃ / min and holding at that temperature for 2h~4h. This invention, by controlling the heating rate, reaction temperature, and time of the heat treatment process, controls the rate of the thermal reduction reaction while ensuring the integrity of the TiC nanotube array, thereby regulating the growth rate of TiC.

[0018] Furthermore, this invention also discloses the application of a porous TiC nanotube array prepared by the method described above as a catalyst support in the field of photoelectrocatalysis.

[0019] Compared with the prior art, the present invention has the following advantages:

[0020] 1. This invention employs an in-situ thermal reduction process for amorphous carbon, using amorphous carbon generated from the thermal decomposition of high molecular weight polyethylene glycol as a reducing agent. This enables the in-situ preparation of porous TiC nanotube arrays at low thermal reduction temperatures and short reaction times, effectively ensuring the structural integrity of the porous TiC nanotube arrays and avoiding product agglomeration and excessive growth that would result in excessively low specific surface area.

[0021] 2. The preparation method of the present invention involves only simple anodizing and heat treatment processes. The required equipment and operating procedures are simple, the process cost is low, and it is suitable for widespread application.

[0022] 3. The porous TiC nanotube array prepared by this invention has the characteristics of large specific surface area and good conductivity, and has shown excellent performance as a support material in the field of photoelectrocatalysis.

[0023] The technical solution of the present invention will be further described in detail below through embodiments. Detailed Implementation

[0024] Example 1

[0025] This embodiment includes the following steps:

[0026] Step 1: Using a 1mm thick titanium foil as the anode and a platinum sheet as the cathode, an anodizing process is adopted. The electrolyte is an ethylene glycol-H2O-ammonium fluoride system, in which the mass content of ethylene glycol is 97.7%, the mass content of H2O is 2%, the mass content of ammonium fluoride is 0.3%, the electrolysis potential is 60V, and the electrolysis time is 2h. An amorphous TiO2 nanotube array is grown on the surface of the titanium foil.

[0027] Step 2: Place the titanium foil with the amorphous TiO2 nanotube array grown on the surface in Step 1 into air and heat-treat it at 400℃ for 2 hours to obtain a crystalline TiO2 NTs / Ti precursor.

[0028] Step 3: Using titanium powder and polyethylene glycol powder with a molecular weight of 6000, the crystalline TiO2NTs / Ti precursor obtained in Step 2 is embedded in a magnetic boat in the following order: titanium powder-polyethylene glycol powder-TiO2NTs / Ti precursor-polyethylene glycol powder-titanium powder. Then, it is placed in a tube furnace and heat-treated in nitrogen: first, it is heated to 350℃ at a heating rate of 5℃ / min and held for 1h, then heated to 800℃ at a heating rate of 10℃ / min and held for 2h to form a porous TiC nanotube array on the surface of the titanium foil.

[0029] Example 2

[0030] This embodiment includes the following steps:

[0031] Step 1: Using 0.5 mm thick sintered porous titanium as the anode and a platinum sheet as the cathode, an anodic oxidation process is adopted. The electrolyte is an ethylene glycol-H2O-ammonium fluoride system, in which the mass content of ethylene glycol is 94.5%, the mass content of H2O is 5%, the mass content of ammonium fluoride is 0.5%, the electrolysis potential is 50 V, and the electrolysis time is 3 h. An amorphous TiO2 nanotube array is grown on the surface of the sintered porous titanium.

[0032] Step 2: The sintered porous titanium with amorphous TiO2 nanotube arrays grown on the surface in Step 1 is placed in air and heat-treated at 300℃ for 3 hours to obtain crystalline TiO2 NTs / Ti precursor.

[0033] Step 3: Using titanium powder and polyethylene glycol powder with a molecular weight of 10,000, the crystalline TiO2NTs / Ti precursor obtained in Step 2 is embedded in a magnetic boat in the following order: titanium powder-polyethylene glycol powder-TiO2NTs / Ti precursor-polyethylene glycol powder-titanium powder. Then, it is placed in a tube furnace and heat-treated in nitrogen: first, it is heated to 350℃ at a heating rate of 5℃ / min and held for 1h, then heated to 700℃ at a heating rate of 10℃ / min and held for 4h, forming a porous TiC nanotube array on the sintered porous titanium surface.

[0034] Example 3

[0035] This embodiment includes the following steps:

[0036] Step 1: Using a 1mm thick titanium mesh as the anode and a platinum sheet as the cathode, an anodizing process is adopted. The electrolyte is an ethylene glycol-H2O-ammonium fluoride system, in which the mass content of ethylene glycol is 99.45%, the mass content of H2O is 0.5%, the mass content of ammonium fluoride is 0.05%, the electrolysis potential is 90V, and the electrolysis time is 2h. An amorphous TiO2 nanotube array is grown on the surface of the titanium mesh.

[0037] Step 2: Place the titanium mesh with amorphous TiO2 nanotube arrays grown on the surface in Step 1 into air and heat-treat it at 600℃ for 0.5h to obtain crystalline TiO2 NTs / Ti precursor;

[0038] Step 3: Using titanium powder and polyethylene glycol powder with a molecular weight of 2000, the crystalline TiO2NTs / Ti precursor obtained in Step 2 is embedded in a magnetic boat in the following order: titanium powder-polyethylene glycol powder-TiO2NTs / Ti precursor-polyethylene glycol powder-titanium powder. Then, it is placed in a tube furnace and heat-treated in argon atmosphere: first, it is heated to 350℃ at a heating rate of 5℃ / min and held for 1h, then heated to 900℃ at a heating rate of 10℃ / min and held for 2h to form a porous TiC nanotube array on the surface of the titanium mesh.

[0039] Example 4

[0040] This embodiment includes the following steps:

[0041] Step 1: Using 2mm thick titanium foam as the anode and platinum sheet as the cathode, anodize the material using an anodic oxidation process. The electrolyte is an ethylene glycol-H2O-ammonium fluoride system, in which the mass content of ethylene glycol is 96.5%, the mass content of H2O is 3%, and the mass content of ammonium fluoride is 0.5%. The electrolysis potential is 70V and the electrolysis time is 2h. An amorphous TiO2 nanotube array is grown on the surface of the titanium foam.

[0042] Step 2: Place the foam titanium with amorphous TiO2 nanotube arrays grown on the surface in Step 1 into air and heat-treat it at 500℃ for 3 hours to obtain crystalline TiO2 NTs / Ti precursor.

[0043] Step 3: Using titanium powder and polyethylene glycol powder with a molecular weight of 8000, the crystalline TiO2NTs / Ti precursor obtained in Step 2 is embedded in a magnetic boat in the following order: titanium powder-polyethylene glycol powder-TiO2NTs / Ti precursor-polyethylene glycol powder-titanium powder. Then, it is placed in a tube furnace and heat-treated in nitrogen: first, it is heated to 350℃ at a heating rate of 5℃ / min and held for 1h, then heated to 800℃ at a heating rate of 10℃ / min and held for 2h to form a porous TiC nanotube array on the surface of the foamed titanium.

[0044] Example 5

[0045] This embodiment includes the following steps:

[0046] Step 1: Using a 0.25mm thick titanium felt as the anode and a platinum sheet as the cathode, an anodizing process is adopted. The electrolyte is an ethylene glycol-H2O-ammonium fluoride system, in which the mass content of ethylene glycol is 98.2%, the mass content of H2O is 1.5%, the mass content of ammonium fluoride is 0.3%, the electrolysis potential is 90V, and the electrolysis time is 0.5h. An amorphous TiO2 nanotube array is grown on the surface of the titanium felt.

[0047] Step 2: Place the titanium felt with amorphous TiO2 nanotube arrays grown on its surface in Step 1 into air and heat-treat it at 400℃ for 1 hour to obtain crystalline TiO2 NTs / Ti precursor.

[0048] Step 3: Using titanium powder and polyethylene glycol powder with a molecular weight of 6000, the crystalline TiO2NTs / Ti precursor obtained in Step 2 is embedded in a magnetic boat in the following order: titanium powder-polyethylene glycol powder-TiO2NTs / Ti precursor-polyethylene glycol powder-titanium powder. Then, it is placed in a tube furnace and heat-treated in nitrogen: first, it is heated to 350℃ at a heating rate of 5℃ / min and held for 1h, then heated to 800℃ at a heating rate of 10℃ / min and held for 3h to form a porous TiC nanotube array on the surface of the titanium felt.

[0049] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention in any way. Any simple modifications, alterations, and equivalent changes made to the above embodiments based on the inventive essence shall still fall within the protection scope of the present invention.

Claims

1. A method for preparing a porous TiC nanotube array, characterized in that, The method includes the following steps: Step 1: Using a titanium substrate as the anode and a platinum sheet as the cathode, an amorphous TiO2 nanotube array is grown on the surface of the titanium substrate using an anodic oxidation process. Step 2: Heat-treat the titanium substrate with amorphous TiO2 nanotube arrays grown on the surface in Step 1 in air to obtain crystalline TiO2 NTs / Ti precursor; Step 3: Using titanium powder and polyethylene glycol powder, the crystalline TiO2 NTs / Ti precursor obtained in Step 2 is embedded in a magnetic boat in the following order: titanium powder-polyethylene glycol powder-TiO2 NTs / Ti precursor-polyethylene glycol powder-titanium powder. Then, it is placed in a tube furnace and heat-treated in an inert atmosphere to form a porous TiC nanotube array on the surface of the titanium matrix. The heat treatment process is as follows: first, heat to 350℃ at a heating rate of 5℃ / min and hold for 1 hour, then heat to 700℃~900℃ at a heating rate of 10℃ / min and hold for 2 hours~4 hours.

2. The method for preparing a porous TiC nanotube array according to claim 1, characterized in that, The titanium substrate mentioned in step one is titanium foil or porous titanium, and the porous titanium is titanium mesh, sintered porous titanium, titanium felt or foam titanium.

3. The method for preparing a porous TiC nanotube array according to claim 1, characterized in that, The electrolyte used in the anodizing process described in step one is an ethylene glycol-H2O-ammonium fluoride system, wherein the mass content of ethylene glycol is 94.5%~99.45%, the mass content of H2O is 0.5%~5%, and the mass content of ammonium fluoride is 0.05%~0.5%.

4. The method for preparing a porous TiC nanotube array according to claim 1, characterized in that, The electrolysis potential of the anodizing process described in step one is 50V~90V, and the electrolysis time is 0.5h~3h.

5. The method for preparing a porous TiC nanotube array according to claim 1, characterized in that, The heat treatment temperature in step two is 300℃~600℃, and the heat treatment time is 0.5h~3h.

6. The method for preparing a porous TiC nanotube array according to claim 1, characterized in that, The molecular weight of the polyethylene glycol powder mentioned in step three is 2000~10000.

7. The method for preparing a porous TiC nanotube array according to claim 1, characterized in that, The inert atmosphere mentioned in step three is nitrogen or argon.

8. The application of a porous TiC nanotube array prepared by the method according to any one of claims 1 to 7 as a catalyst support in the field of photoelectrocatalysis.

Citation Information

Patent Citations

  • Method for in-situ growth of TiC nanotubes

    CN111620340A

  • Systems including nanotubular arrays for converting carbon dioxide to an organic compound

    US20100258446A1